Development Strategy of Soy Sauce Business in Purwodadi District Grobogan Regency - Tamara, Ervina Ayu; Prajanti, Sucihatiningsih Dian Wisika; Oktavilia, Shanty (Journal of Economic Education, 2024)
The numerous of soy sauce factories that are spread throughout Indonesia, such as Udang and Bawang soy sauce brands are two of the industry players that are most well-known in Grobogan Regency and its surrounding area. This research aimed to discover the strategy used in soy sauce business development in Purwodadi District, Grobogan Regency. The population of this research used a keyperson that consisted of 3 people. The method used in this research is a mixed method and used descriptive qualitative, Analytical Hierarchy Process (AHP) and Matrix of Alliance, Conflicts, Tactics, Objectives, and Recommendations (MACTOR) to analyze the result. The research subjects are government policy, human resources, and institutional. The result shows based on AHP analysis, the priorities of business development strategy are as follows (1) government policy criteria in the amount of 0.402; (2) Human resource criteria in the amount of 0.402; (3) Institutional criteria in the amount of 0.144. Furthermore, in the MACTOR analysis stated that there are 6 actors and 7 goals that have a role in the effort to develop the soy sauce business, distributor, retailer, consumer, and raw materials supplier. Meanwhile, there are 2 most significant objectives namely Increasing Promotional and Marketing Capability and synergy in Increasing Productivity. The suggestion from this study is that the most prioritized policies are on providing training and facilitating business licensing, promotion, and marketing training. Meanwhile, for further research, can develop existing research by adding, comparing or evaluating the results of variables and analysis to be more complex, comprehensive, and integrated.